Igreja, sindicato e organização dos trabalhadores - Albuquerque, Ronald de Figueiredo e (1991)
In this study, we analyzed the organization of the trabalhares rural municipality of Crato, in view of the role played by the Diocese of Crato in the creation of unions throughout the region. These unions are allowed in the first instance, the discussion of problems involving field workers, creating a wave nonexistent before the meeting was possible allowing visualization of reality seen by each life. The diocese has taken the path when the union does not want to radicalize the opposition between landowners and workers, between workers and the state as an instrument of domination. His first project was aimed at improving the living conditions of the workers but within the established bourgeois order, was his intention, as is shown here, to resume the work of Fr Ibiapina to create rural communities where the farmer had attended some reclamations allowing the "peace" and order through mediation conducted by the State in meeting the most urgent demands of the workers. At first, partnering with local diocese concerns of the entire Catholic Church in Brazil create impediments to organizing workers left, especially the Communist Party, and then creates unions to focus their concern with the communities until a time when the break between the foundation and the proceeds diocese because he could not be within your project, take the fight radicalization of workers desired by them and their needs. Thus, we analyze the reasons that led the Catholic Church to seek the beginning, the organization of workers after the insertion of the Diocese of Crato this process ple showing peculiarities to be geared more to local realities, their relationship with workers in the region and changes that this process suffers as a result of a national situation that changes, resulting in different behaviors on the part of the Church (local diocese), workers and team ELIRUR (School of Rural Leaders). On the other hand, there is also a trade union organization in the transformations consequences of policy changes in the context of post-stroke 64 and the consequences Cariri, specializing in the municipality of Crato. The unions in the region do not suffer from the blow but his relationship with the workers, the staff and the ELIRUR Own diocese becomes, especially after 72, moving away from the diocese seeking work from parameters imposed by the dictatorship. Back to the action of the diocese and the School of Rural Leaders Foundation Fr Ibiapina more for the rural community, especially ELIRUR passing your work done within a perspective of change in production relations existing. This action of ELIRUR is subsequently confronted with the goals of the diocese that alienates its members more expressive and thus moving away from community leaders who choose to stay together dissident members of the diocese creating an entity to continue the monitoring of agricultural communities within a more radical, and entirely independent Mayan oriented needs.